Dendritic cell‐derived exosomes carry the major cat allergen Fel d 1 and induce an allergic immune response. Issue 12 (25th August 2015) - Vallhov, H.; Gutzeit, C.; Hultenby, K.; Valenta, R.; Grönlund, H.; Scheynius, A.
Abstract: Exosomes are nano‐sized membrane vesicles (50–120 nm), which are released from a wide variety of cells. Depending on their cellular origin, they can induce immune stimulatory‐, inhibitory‐, or tolerance‐inducing effects. However, it is still unclear what role exosomes play during human inflammatory diseases. It has not been studied whether exosomes derived from human dendritic cells (DCs), the first cells to encounter allergens in the mucosa, can carry aeroallergens and contribute to allergic immune responses. We therefore explored whether DC‐derived exosomes can present the major cat allergen Fel d 1 and whether they thereby contribute to the pathogenesis of allergic disease. Our results demonstrate that exosomes are able to present aeroallergens and thereby induce T‐cell T(H)2‐like cytokine production in allergic donors. Thus, these exosomes may be important immune‐stimulatory factors in allergic immune responses and important targets or engineered tools in immunotherapy.